Salmonella spp. Isolated by Miniaturized Most Probable Number and Conventional Microbiology in Poultry Slaughterhouses - Mion, Ligiani; Parizotto, Luana; Santos, Lilian Andriva dos; Webber, Bruna; Cisco, Isabel Cristina; Pilotto, Fernando; Rodrigues, Laura Beatriz; Nascimento, Vladimir Pinheiro do; Santos, Luciana Ruschel dos (Acta Scientiae Veterinariae, 2016)
Background: Salmonella spp. are frequently isolated from fowls, and their detection in poultry products varies according to the breeding system and the slaughtering process, bringing risks to the consumer and compromising the marketability. The control of Salmonella in poultry slaughterhouses is based on the detection of bacteria, but the quantification of the agent would be important in assessing risk, as well as in obtaining data to determine the capacity of each step of the process to decrease or increase bacterial contamination. The aims of this study were to propose a method for the quantification of Salmonella in poultry slaughterhouses, frequency of isolation and serovars identified. Materials, Methods & Results: Twenty-one broiler flocks from seven federally inspected slaughterhouses in southern Brazil, totaling 1,071 samples, were assessed by miniaturized most probable number (mMPN) and conventional microbiology. The samples were collected in triplicate at 17 points, which included cloacae, transportation cages before and after sanitization, water (scald tank, supply, pre-chiller and chiller), and carcasses (before and after scalding, defeathering, rinsing, evisceration, final rinsing, chilling at 4ºC, and freezing at -12°C for 24 h, 30 and 60 days). Typical Salmonella colonies were submitted to TSI, LIA, SIM, urea, and polyvalent anti-O antiserum tests, and to final identification by Microarray by Check&Trace. Nine of the 1,071 (0.83%) samples analyzed by mMPN and by conventional microbiology were positive for Salmonella and the following serovars were identified: Anatum, Brandenburg, Agona, Tennessee, Bredeney, Schwarzengrund and Infantis. Discussion: This positive rate was lower than that described by other authors, whose rates ranged from 3% and 39% for the isolation of Salmonella spp. from different sources, such as slaughterhouses and retail sales in samples collected in Brazil. The low frequency of isolation of Salmonella in this study can be attributed to the efficiency of control systems used from the field to the slaughterhouse, such as Good Manufacturing Practices (GMP) and Sanitation Standard Operating Procedures (SSOP), which are HACCP requirements. Also, when slaughtering technology actions are properly managed, such as water replacement and temperatures lower than 4ºC in the chiller, the initial contamination by Salmonella spp. can be reduced, with a decline in contamination from 70% to 20%, and with a reduction in the contamination of broiler carcasses after chilling from 15.8% to 3.3%. On the other hand the contamination of carcasses by Salmonella before pre-chilling and in post-chilling might be due to the automated system, inadequate temperatures during chilling, and inappropriate water chlorination in the assessed meat-packing plant. Of the 17 points evaluated, seven were positive for Salmonella, especially the cages after sanitization and frozen carcasses. The contamination by Salmonella spp. in transportation cages after sanitization indicates inefficiency of the automated system as well as possible bacterial resistance to the sanitizers used in SSOP while the isolation in carcasses frozen for 24 h and 60 days demonstrates the thermal resistance of the bacterium to a conservation method widely used in the food industry. In this work, just one of the nine positive samples for Salmonella was identified by conventional methods (CM) and mMPN. The discrepancy between methods can be explained by the heterogeneous distribution of Salmonella and other bacteria in naturally contaminated samples. Samples that were positive in the qualitative test but negative in the mMPN protocol could have had a number of Salmonella below the detection amount.